Pertimbangan Hakim Dalam Memutuskan Perkara Perceraian Dengan Alasan Murtad - ulfi muflikhah; triana sofiani (Al-Hukkam: Journal of Islamic Family Law, 2022)
Apostasy in fiqh can be used as a cause for the breakup of a marriage. Many divorce cases are handled by the Religious Courts. One of them is two cases of divorce cases that occurred between the applicant and the respondent but of different religions. There is a disparity in the two decisions, in Decision Number: 1808/Pdt.G/2017/Pa.Pwt and Decision Number: 426/Pdt.G/2020/Pa.Pkl. The two decisions above have similarities in illat, namely one of the spouses both apostates, but there are differences in judges in deciding the divorce case where in Decision Number: 1808/Pdt.G/2017/Pa.Pwt the judge decided on the imposition of talak ba'in sughro, while in Decision Number: 426/ Pdt.G/2020/Pa.Pkl the judge terminated the marriage relationship between the applicant and the respondent with Fasach. This research is a normative juridical research and uses a statute approach, a conceptual approach, a comparative approach and a case approach. The results of this study are the judges' considerations in passing a divorce decision on the grounds of apostasy in Decision Number 1808/Pdt.G/2017/Pa.Pwt with talak one ba'in shughraa because the judge views that the main factor in divorce is quarrels and disputes that occur regularly. continuously because the Respondent apostatized and in accordance with Article 119 regarding the divorce of one ba'in shughraa, while Decision Number 426/Pdt.G/2020/Pa.Pkl was terminated by terfasakh their marriage because it took into account the concept of Islamic law where the Petitioner had no right to refused because he had apostatized.